INCORRECT VOCABULARY AND SYNTAX IN THE SPEECH OF PROFESSIONALS: AN ANTITHESIS OF SCIENTIFIC LANGUAGE - López Gómez, Eugenio Jesús (2019)
Th ere is a widespread situation in the Villa Clara Medical School. Th is has to do with an increase of verbose language spoken by professors and the incorrect use of vocabulary and syntax, which has resulted in stereotypes due to recurrent use. Th is fact aff ects the professional communicative competence and logically contradicts the principles and rules of scientifi c communication. Th erefore, the objective of this study was to analyze the contradiction between the abovementioned linguistic irregularities and the characteristics of scientifi c language. During the research, theoretical methods were applied —analysis-synthesis, induction-deduction—, and empirical methods —observation and document review—, besides the systematic exchange with professionals of the school. Th is allowed analysis and systematization of the collected data to arrive at reliable conclusions. Most recurrent lexical-syntactic errors and stereotypes were verifi ed: stereotyped words and expressions, non-accepted fashion words by the Royal Academy of the Spanish Language and lexical improprieties. In short, the situation denotes cognitive lack of linguistic rules and principles in the speech of professors. There is a tedious and monotonous atmosphere that aff ects the verbal image and signifi es the antithesis of scientifi c communication, which is based on precision, clarity, and concretion of the message.